EFFECTS OF RENAL DENERVATION ON BLOOD PRESSURE IN PATIENTS WITH END-STAGE RENAL DISEASE: A SINGLE CENTER EXPERIENCE. (June 2018) - Ott, C.; Schmid, A.; Ditting, T.; Veelken, R.; Uder, M.; Schmieder, R.E.
Abstract : Objective: Sympathetic nerve activity is a hallmark of hypertension in end-stage renal disease (ESRD). An initial proof-of-concept study implies that renal denervation (RDN) is feasible and safe in RDN, but overall data are limited. Design and method: In this single-centre prospective pilot study 6 patients with ESRD and treatment resistant hypertension were consecutively included. Ambulatory blood pressure (ABP) was measured before and 6 months after RDN (Symplictiy Flex™, Medtronic Inc., Santa Rosa, CA). Moreover, hemodialytic parameters which may impact on BP-reduction were monitored closely. Results: In all patients bilateral RDN was successful done, without documentation of peri- or postprocedural complications. There was a significant reduction in 24-h ABP by -20 ± 17 / 15 ± 12 mmHg 6 months after RDN (systolic: 163 ± 16 vs. 143 ± 9 mmHg, p = 0.043; diastolic: 96 ± 9 vs. 81 ± 15 mmHg, p = 0.043), with similar results for day-, and nighttime values, respectively. Antihypertensive medication was kept stable as well as there was no change in hemodialysis parameters during follow-up. In addition, ultrafiltration/week (1.4 ± 1.4 versus 2.2 ± 1.4 l, p = 0.08) as well as hematocrit (measured at baseline and 6 months after RDN) (33.7 ± 4.3 versus 33.1 ± 3.9 %, p = 0.715) revealed no change in volume status. Conclusions: Our single-center pilot study support current data on renal safety of RDN even in small arteries of patients with ESRD, but also expand the knowledge towards an effective ABP-reduction.